ANALISIS KEBUTUHAN MAHASISWA TERHADAP BAHAN AJAR SEBAGAI ACUAN UNTUK MENGEMBANGKAN E-MODUL PEMBELAJARAN DIGITAL - Dewi Pratita; Dian Eka Amrina; Yulia Djahir (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2021)
This research aims to analyze students needs for teaching materials used in Digital Learning lecture activities. This research is an exploratory descriptive study with the sample of research is Economics Education students at fifth semester FKIP Sriwijaya University who are in two classes namely regular classes and extension classes as many as 79 students. Research data is obtained from preliminary observations showed that in the materials of Digital Learning lectures will be more practical in creating content in Digital Learning because of the limited time that only two credits at each meeting can make it difficult for lectures to provide detailed explanations of the material to students. The results of the students questionnaire analysis show that students need more digital type teaching materials in the from modules in order to be supportive in student lecture activities.